Colorectal cancer surveillance by colonoscopy in a prospective, population-based long-term Swiss screening study – outcomes, adherence, and costs - Zgraggen, Armin; Stoffel, Sandro Tiziano; Barbier, Michaela Carla; Marbet, Urs Albert (Zeitschrift für Gastroenterologie, 2022)
Background The success of colorectal cancer (CRC) screening depends mainly on screening quality, patient adherence to surveillance, and costs. Consequently, it is essential to assess the performance over time.Methods In 2000, a closed cohort study on CRC screening in individuals aged 50 to 80 was initiated in Uri, Switzerland. Participants who chose to undergo colonoscopy were followed over 18 years. We investigated the adherence to recommended surveillance and collected baseline characteristics and colonoscopy data. Risk factors at screening for the development of advanced adenomas were analyzed. Costs for screening and follow-up were evaluated retrospectively.Results 1278 subjects with a screening colonoscopy were included, of which 272 (21.3%; 69.5% men) had adenomas, and 83 (6.5%) had advanced adenomas. Only 59.8% participated in a follow-up colonoscopy, half of them within the recommended time interval. Individuals with advanced adenomas at screening had nearly five times the risk of developing advanced adenomas compared to individuals without adenomas (24.3% vs. 5.0%, OR 4.79 CI 2.30–9.95). Individuals without adenomas developed advanced adenomas in 4.9%, including four cases of CRC; three of them without control colonoscopy. The villous component in adenomas smaller than 10 mm was not an independent risk factor. Costs for screening and follow-up added up to CHF 1’934’521 per 1’000 persons screened, almost half of them for follow-up examinations; 60% of these costs accounted for low-risk individuals.Conclusion Our findings suggest that follow-up of screening colonoscopy should be reconsidered in Switzerland; in particular, long-term adherence is critical. Costs for follow-up could be substantially reduced by adopting less expensive long-term screening methods for low-risk individuals.
Keywords: Adenom; Karzinom; Koloskopie; Kolorektales Adenom; Kolorektales Karzinom; Kolorektale Polypen; Vorsorgeuntersuchung